PENGARUH KURS,SUKU BUNGA,INFLASI DAN JUMLAH UANG BEREDAR TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA TAHUN 2014-2022 - Mohammad Farhan; Ghozali Maski (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to investigate the influence of exchange rates, interest rates, inflation, and money supply on the Composite Stock Price Index (IHSG) at the Indonesia Stock Exchange during the period 2014-2022 using multiple linear regression analysis. The study utilizes secondary data obtained from Bank Indonesia, the Indonesia Stock Exchange, and the Central Statistics Agency. The analysis reveals that among the four independent variables examined, only the exchange rate significantly influences the IHSG. Specifically, changes in the exchange rate have a significant impact on the movement of the IHSG in the Indonesian capital market. Meanwhile, interest rates, inflation, and money supply do not show significant effects on the IHSG during the studied period. These findings provide valuable insights for investors and policymakers to understand the factors influencing the IHSG movements in the Indonesian stock market. The practical implication of this research underscores the importance of considering exchange rate factors in formulating investment strategies in the Indonesian stock market.